2018
DOI: 10.3390/catal8040137
|View full text |Cite
|
Sign up to set email alerts
|

The First Catalytic Direct C–H Arylation on C2 and C3 of Thiophene Ring Applied to Thieno-Pyridines, -Pyrimidines and -Pyrazines

Abstract: A practical one-pot procedure for the preparation of diverse thieno [3,2-d]pyrimidines is reported here for the first time. This two-step process via C-H activation in position C-2 of thiophene led to the development of an improved methodology for the synthesis of numerous compounds. This new methodology is an efficient alternative to the conventional methods currently applied. The C-H activation of the thiophene C-3 position was also achieved and can be selective. The optimized conditions can also be applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Using the conditions described in our previous work the precursor of palladium CH direct arylation, 4‐(5‐methyl‐2‐phenyl‐1 H ‐pyrazolo[1,5‐ a ]pyrimidin‐7‐yl)morpholine ( 3 ) was synthesized by S N Ar with morpholine as amine reagent in toluene, in 69 % yield after 24 hours of heating at 130 °C, (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the conditions described in our previous work the precursor of palladium CH direct arylation, 4‐(5‐methyl‐2‐phenyl‐1 H ‐pyrazolo[1,5‐ a ]pyrimidin‐7‐yl)morpholine ( 3 ) was synthesized by S N Ar with morpholine as amine reagent in toluene, in 69 % yield after 24 hours of heating at 130 °C, (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…A low quantity of the expected compound was obtained using Pd(OH) 2 /C in DMA (Table , Entry 9). We also investigated the role of ligand and/or base on this cross‐coupling Pd‐catalyzed direct arylation reaction and we found that the use of P t Bu 3 HBF 4 , instead of PPh 3 in the presence of 10 mol‐% of Pd(OAc) 2 , bromobenzene (1.5 equiv. ), and K 2 CO 3 (2 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, we related for the first time a procedure of CÀ H activation on the thiophene ring in thieno [3,2-b]pyridines, thieno [3,2-d]pyrimidines and thieno [2,3-b]pyrazines. [8] To the best of our knowledge, to this day nothing similar has been published. A study of the literature revealed that in addition to the three teams (Figure 2, b-d) we described in the previous publication, one new study of CÀ H arylation of fused thiophenes was reported (Figure 2, a).…”
Section: Introductionmentioning
confidence: 99%
“…This reaction has played an important role in the elaboration of numerous compounds in many fields and is probably one of the most studied cross-coupling reactions in organic and medicinal chemistry. Sangeeta Jagtap has summarized many reviews on this topic mainly about catalysts, ligands and various conditions used but also suggested mechanisms.Damien Prim's group worked on acridines, aza-polycyclic compound having a broad range of properties and applications in therapeutic, pigments, dyes, imaging probes, sensor and some other materials activities [5]. The 5,6-dihydrobenzo[c]acridine, comprises of four fused cycles of which one is partially hydrogenated leading to not fully planar compounds usable in the preparation of helical-shaped molecules.…”
mentioning
confidence: 99%
“…Damien Prim's group worked on acridines, aza-polycyclic compound having a broad range of properties and applications in therapeutic, pigments, dyes, imaging probes, sensor and some other materials activities [5]. The 5,6-dihydrobenzo[c]acridine, comprises of four fused cycles of which one is partially hydrogenated leading to not fully planar compounds usable in the preparation of helical-shaped molecules.…”
mentioning
confidence: 99%